Analysis Of The Impact Of Burn Money Strategy On The Financial Performance Of Startups In West Nusa Tenggara (NTB) - Berlin, Hertha (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
The growth of digital startups in Indonesia is increasing, particularly through burn money strategies to accelerate market acquisition. However, implementing this strategy often challenges financial stability, especially for startups with limited access to funding, such as those in West Nusa Tenggara (NTB) Province. This study aims to analyze the impact of burn money strategies on the financial performance of digital application startups in NTB. The research uses a qualitative approach with a case study method, collecting data through in-depth interviews and observations of three startups that apply this strategy.The findings show that burn money strategies boost user growth and competitiveness and create significant pressure on liquidity and cash flow. Successful startups practice disciplined financial management, limit expenses, and regularly evaluate their strategies. On the other hand, startups that are too aggressive without solid financial planning struggle to sustain long-term operations. This study emphasizes the importance of innovation, good governance, and structured financial and risk management in maintaining the sustainability of startups in the digital era. These findings provide valuable input for startup actors and stakeholders in designing sustainable growth strategies.